The relationship between first year engineering students' perceptions of workload and stress - Lindsay, Euan (Melbourne School of Engineering, University of Melbourne, 2009)
Engineering degree programs are notorious for placing considerable demands upon their students. Balancing study and work is a challenge faced by an increasing number of undergraduate students. There is an implicit assumption that an increase in workload results in more stress for the students; however a closer examination of the situation reveals greater complexity. This paper presents data gathered in a semester-long weekly survey of first year engineering students. Students were asked to rate their stress levels and workload relative to normal, and they were also asked to give an absolute rating for their stress levels. Their self-reported levels of workload and stress are compared to each other and to the number of hours reported for study and paid employment. This comparison shows that while in general workload and stress are indeed linked, there is a substantial proportion of the cohort for whom these factors appear to be independent. In particular the link between absolute stress and workload appears weaker, suggesting that the issue may not be the actual level of stress, but rather the students’ perceptions of what constitutes a “normal” workload at a university level.